Preparation of WO3/rGO/BiOBr and its photocatalytic degradation performance for ciprofloxacin wastewater - ZHOU Chaoyun; LING Yulin; JIANG Wenxue; ZHOU Jianhong (Gongye shui chuli)
The composite photocatalyst WO3/rGO/BiOBr(WRB) was prepared by solvothermal method. BiOBr was assembled into the WO3 nanotube beam loaded with rGO. WRB was characterized by X-ray diffraction(XRD), scanning electron microscopy(SEM), Fourier infrared spectroscopy(FT-IR) and UV-Visible spectrophotometry(UV-Vis). Using the removal rate of ciprofloxacin(CIP) as the optimization index, single factor experiments were conducted to investigate the effects of composite material ratio, dosage, solution pH, and light conditions on the photocatalytic degradation performance of CIP by WRB. The results showed that BiOBr was uniformly grown on the WO3 rods covered by the rGO membrane, with changing the light absorption performance. A 500 W Xenon lamp was used as the irradiation light source, and WRB-40 with a theoretical WO3 mole fraction of 40%(rGO added at 1% of WO3 mass) was used as the composite catalyst. Under the conditions of WRB-40 dosage of 0.67 g/L, solution pH of 9.07, and illumination time of 120 min, the CIP degradation effect by WRB reached its optimum, with a degradation rate of 96.51%. In addition, CIP degradation rate remained 88.5% after four cycles experiment, indicating WRB had high catalytic efficiency and great stability. Embedding a thin layer of rGO between WO3 and BiOBr was more conducive to the transmission of photo-generated carriers, which effectively improved the performance of heterojunction.